2016
DOI: 10.18632/oncotarget.10178
|View full text |Cite
|
Sign up to set email alerts
|

Expected long-term impact of screening endoscopy on colorectal cancer incidence: a modelling study

Abstract: BACKGROUND & AIMSScreening endoscopy reduces colorectal cancer (CRC) incidence but the time course and magnitude of effects beyond 10 years after screening are unknown. We aimed to estimate the expected time course and magnitude of long-term impact of screening endoscopy on CRC incidence.METHODSWe used Markov models based on the natural history of the disease along with data from the German national screening colonoscopy registry to derive the expected impact of screening colonoscopy at age 55 or 60 on cumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
2
15
0
1
Order By: Relevance
“…For CRC mortality, no initial increase occurs, and, as confirmed by our models, an even stronger reduction is expected, with relative mortality reduction after a single colonoscopy reaching its maximum already after 12–13 years. This is 2–3 years earlier than the maximum of relative reduction of cumulative incidence, which, according to our previous study is expected after 15 years …”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…For CRC mortality, no initial increase occurs, and, as confirmed by our models, an even stronger reduction is expected, with relative mortality reduction after a single colonoscopy reaching its maximum already after 12–13 years. This is 2–3 years earlier than the maximum of relative reduction of cumulative incidence, which, according to our previous study is expected after 15 years …”
Section: Discussionsupporting
confidence: 66%
“…Previous studies on CRC incidence have shown that the protective effect of screening against CRC only became apparent after at least 4–5 years because of the detection of prevalent asymptomatic cancers at screening . While screening clearly does not prevent the occurrence of existing cases, these screen‐detected patients still benefit from early detection and timely treatment and have better chances of cure .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, despite these limitations, our study suggests that introduction of screening colonoscopy as an alternative screening offer in Germany increased adherence to CRC screening overall, with screening colonoscopy becoming the primary source for being up‐to‐date with CRC screening after 5–6 years. These encouraging results, along with model‐based projections, suggest that major reduction of CRC incidence and mortality is to be expected in the years and decades to come, which has already started to become evident in recent years and which could potentially be further enhanced by switching to an organized CRC screening program.…”
Section: Discussionmentioning
confidence: 89%